Standard term concrete families on the example of continuous production of Spiroll slabs - Jasiczak, Józef; Kanoniczak, Marcin; Smaga, Łukasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article presents the division of test results series for the compressive strength of concrete into concrete families for the continuous production of concrete mix used for the manufacture of precast concrete slabs in Spiroll technology. On the basis of a calculation procedure involving the verification of assumed statistical hypotheses, the division of a set of concrete strength results achieved after 1 and 28 days of curing was made. Concrete families were obtained representing the statistical invariability of strength parameters for the concrete manufactured in a defined period of time.